Usability and feasibility of E-nergEYEze: a blended vision-specific E-health based cognitive behavioral therapy and self-management intervention to reduce fatigue in adults with visual impairment - M.H.J. Veldman; H.P.A. van der Aa; H. Knoop; C. Bode; C.T.J. Hulshof; L. van der Ham; G.H.M.B. van Rens; M.W. Heymans; R.M.A. van Nispen (BMC, 2023)
Abstract Background Over 50% of adults with visual impairment experience severe fatigue. Therefore, we developed a guided E-health intervention based on cognitive behavioral therapy and self-management to reduce fatigue in this population. This pilot study evaluated the usability, feasibility, fidelity and potential effectiveness of E-nergEYEze. Methods E-nergEYEze was developed by a design team and customized by conducting a pilot study using an iterative development strategy. The intervention was first tested in a usability study among adults with visual impairment (n = 5). Participants were asked to think-aloud while exploring the intervention features and a semi-structured interview was performed afterwards. Subsequently, the enhanced intervention was tested in a feasibility study. Adults with visual impairment and severe fatigue (n = 10) followed the intervention partially with guidance from a social worker and one-time computer trainer support. Fatigue severity (Checklist Individual Strength), fatigue impact (Modified Fatigue Impact Scale) and cognitive behavioral therapy skills (Competencies of Cognitive Therapy Scale-Self Report) were measured at baseline and at three months follow-up and analyzed with the Wilcoxon signed-rank test. The intervention was evaluated through evaluation forms. Results The usability study resulted in adjustments to content and lay-out with regard to optically shortened text sentences, separate pages for information and assignments with one read-aloud audio and an additional descriptive explanation of page content. Digital challenges were overcome with mandatory computer training and e-platform modifications. The feasibility study showed a positive trend in reducing fatigue severity (Z -6.108; P < .001; SD 8.4), impact of fatigue (Z − 4.451; P < .001; SD 11.4) and cognitive behavioral therapy skills (Z -2.278; P = .023; SD 19.3). Participants gave useful feedback regarding accessibility, content and guidance, with an overall positive experience. The intervention was rated with a median score of 8 (range 7-10). Conclusion We developed, evaluated and optimized E-nergEYEze by applying a user-centered and iterative approach. E-nergEYEze showed a promising trend to reduce fatigue severity and impact of fatigue and to increase cognitive behavioral therapy skills. The study methods were feasible and the fidelity of the intervention protocol was suitable. Performing a randomized controlled trial is warranted to give insight into whether E-nergEYEze is cost-effective in reducing severe fatigue in adults with visual impairment. Trial registration International Clinical Trial Registry Platform: NL7764. Date registered: 28-05-2019.